Local wisdom-based hotel management strategy in strengthening the destination branding of Tanah Karo tourism - Daniel Sihombing; Sontina Griche Tambunan (Trigin Publisher, 2026)
Tourism development increasingly emphasizes local wisdom as a strategic asset in strengthening destination identity and competitiveness. This study analyses a local wisdom-based hotel management strategy at Sibayak Berastagi Hotel and its contribution to the destination branding of Tanah Karo. An interpretive qualitative case-study design was applied to a structured dataset comprising 18 role-based informants: three managers, five operational employees, six hotel guests, one tourism-office representative, one Karo cultural leader, and two local micro-enterprise actors. Data were analysed through open, axial, and selective coding using an interactive qualitative analysis approach. Source and method triangulation, a codebook, an audit trail, an evidence matrix, and contextual description were used to strengthen trustworthiness. The analysis identified four interconnected themes: cultural orientation in management, the translation of mehamat into service behaviour, cultural products and spatial identity, and community collaboration. These practices create culturally meaningful guest touchpoints that strengthen perceived authenticity and destination differentiation. The study proposes a Cultural Hospitality–Destination Branding pathway that links local values, managerial translation, guest experience, and destination-brand outcomes.